Characterization of mesenchymal stem cells derived from equine adipose tissue - Carvalho, A.m. [UNESP] (2013)
Stem cell therapy has shown promising results in tendinitis and osteoarthritis in equine medicine. The purpose of this work was to characterize the adipose-derived mesenchymal stem cells (AdMSCs) in horses through (1) the assessment of the capacity of progenitor cells to perform adipogenic, osteogenic and chondrogenic differentiation; and (2) flow cytometry analysis using the stemness related markers: CD44, CD90, CD105 and MHC Class II. Five mixed-breed horses, aged 2-4 years-old were used to collect adipose tissue from the base of the tail. After isolation and culture of AdMSCs, immunophenotypic characterization was performed through flow cytometry. There was a high expression of CD44, CD90 and CD105, and no expression of MHC Class II markers. The tri-lineage differentiation was confirmed by specific staining: adipogenic (Oil Red O), osteogenic (Alizarin Red), and chondrogenic (Alcian Blue). The equine AdMSCs are a promising type of adult progenitor cell for tissue engineering in veterinary medicine.